Structural Insight into Layer Gliding and Lattice Distortion in Layered Manganese Oxide Electrodes for Potassium‐Ion Batteries. Issue 30 (28th June 2019) - Zhang, Qing; Didier, Christophe; Pang, Wei Kong; Liu, Yajie; Wang, Zhijie; Li, Sean; Peterson, Vanessa K.; Mao, Jianfeng; Guo, Zaiping
Abstract: Potassium‐ion batteries (PIBs) are an emerging, affordable, and environmentally friendly alternative to lithium‐ion batteries, with their further development driven by the need for suitably performing electrode materials capable of reversibly accommodating the relatively large K + . Layer‐structured manganese oxides are attractive as electrodes for PIBs, but suffer from structural instability and sluggish kinetics of K + insertion/extraction, leading to poor rate capability. Herein, cobalt is successfully introduced at the manganese site in the K x MnO2 layered oxide electrode material and it is shown that with only 5% Co, the reversible capacity increases by 30% at 22 mA g ‐1 and by 92% at 440 mA g ‐1 . In operando synchrotron X‐ray diffraction reveals that Co suppresses Jahn–Teller distortion, leading to more isotropic migration pathways for K + in the interlayer, thus enhancing the ionic diffusion and consequently, rate capability. The detailed analysis reveals that additional phase transitions and larger volume change occur in the Co‐doped material as a result of layer gliding, with these associated with faster capacity decay, despite the overall capacity remaining higher than the pristine material, even after 500 cycles. These results assert the importance of understanding the detailed structural evolution that underpins performance that will inform the strategic design of electrode materials for high‐performance PIBs. Abstract : A reduction of Jahn‐Teller distortion at most states‐of‐charge is achieved via 5% cobalt doping in P′3‐type K x MnO2 . The doped material exhibits significantly improved reversible capacity and diffusion rate of K + as a cathode in potassium‐ion batteries. In operando synchrotron XRD revealed a series of phase transformations during cycling, with layer gliding transitions that may affect the long‐term stability of the electrode.